2013
DOI: 10.1021/ja3119527
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Sum Frequency Generation for In Situ Probing Proton Exchange in Antiparallel β-Sheets at Interfaces

Abstract: Studying hydrogen/deuterium (H/D) exchange in proteins can provide valuable insight on protein structure and dynamics. Several techniques are available for probing H/D exchange in the bulk solution, including NMR, mass spectroscopy, and Fourier transform infrared spectroscopy. However, probing H/D exchange at interfaces is challenging because it requires surface-selective methods. Here, we introduce the combination of in situ chiral sum frequency generation (cSFG) spectroscopy and ab initio simulations of cSFG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
168
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(182 citation statements)
references
References 58 publications
(89 reference statements)
10
168
1
Order By: Relevance
“…70 For example, Figure 8A shows the chiral SFG spectrum of the peptide of LK 7 β obtained using the psp polarization setting at the air/water interface. 84 The peptide, with a sequence of LKLKLKL, is highly amphiphilic and is known to form antiparallel β-sheet at the air/water interfaces. 102 The peptide was dissolved in phosphate buffer (10 mM, pH 7.4).…”
Section: Chiral N−h Stretch From Protein Backbone At Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…70 For example, Figure 8A shows the chiral SFG spectrum of the peptide of LK 7 β obtained using the psp polarization setting at the air/water interface. 84 The peptide, with a sequence of LKLKLKL, is highly amphiphilic and is known to form antiparallel β-sheet at the air/water interfaces. 102 The peptide was dissolved in phosphate buffer (10 mM, pH 7.4).…”
Section: Chiral N−h Stretch From Protein Backbone At Interfacesmentioning
confidence: 99%
“…The observation of protein backbone chiral N−H stretch with zero water background has introduced the opportunity of probing real-time H/D exchange in protein at interfaces. 84 The experiments were performed using a model system of the amphiphilic LK 7 β peptide, which forms antiparallel β-sheet structures at the air/water interface ( Figure 16A). This peptide exhibits chiral SFG spectra in amide I regions at the air/H Figure 16B This work demonstrates a novel application of chiral SFG: probing H/D exchange of proteins at interfaces in situ and in real time.…”
Section: Kinetics Of Proton Exchange In Protein Backbones Probed By Cmentioning
confidence: 99%
“…2628 We have monitored, in situ and in real time, the misfolding of human islet amyloid polypeptide (hIAPP) into parallel β -sheets via an α-helical intermediate at the lipid/water interface, 26, 2829 and proton exchange in parallel β–sheets at interfaces. 30 We have also demonstrated that chiral SFG can be used to determine the orientation of the parallel β -strand of hIAPP aggregates at interfaces by analyzing the chiral amide I spectrum. 28, 3132 …”
mentioning
confidence: 90%
“…[8][9][10][11][12][13][14] While CD-spectroscopy is a linear optical technique, the enantiomer-specificity of which results from inherently weak magnetic dipole or electric quadrupole interactions, the potential of non-linear optical techniques such as second harmonic generation (SHG) and sum-frequency generation (SFG) to study chiral molecules has been increasingly recognized over the past years. [15][16][17][18][19][20][21][22][23][24][25] Vibrational SFG-spectroscopy (VSFG) is a second-order non-linear optical technique, in which an infrared pulse and a visible pulse are combined to generate light at their sum-frequency. This generation is enhanced in case the infrared light is in resonance with specific molecular vibrations.…”
mentioning
confidence: 99%
“…Recently, chiral VSFG-spectra have been successfully measured for protein monolayers in the spectral region of the amide I vibration (C= =O-stretch) and the NH-stretch vibration, 19,[21][22][23] which allowed, e.g., to obtain unprecedented insights into the aggregation mechanism of amyloidic peptides at water-lipid interfaces. 22 While these studies have focussed on the intensity of the generated SFG-light I s f g ∝ | χ (2) | 2 , the sign of the non-linear susceptibility χ changes between enantiomers, and thus, information on the absolute configuration of chiral molecules can be obtained if the real and imaginary parts of χ (2) chiral are determined.…”
mentioning
confidence: 99%